The North American bullfrog draft genome provides insight into hormonal regulation of long noncoding RNA. Issue 1 (December 2017) - Hammond, S. Austin; Warren, René; Vandervalk, Benjamin; Kucuk, Erdi; Khan, Hamza; Gibb, Ewan; Pandoh, Pawan; Kirk, Heather; Zhao, Yongjun; Jones, Martin; Mungall, Andrew; Coope, Robin; et al.
Abstract Frogs play important ecological roles, and several species are important model organisms for scientific research. The globally distributed Ranidae (true frogs) are the largest frog family, and have substantial evolutionary distance from the model laboratoryXenopus frog species. Unfortunately, there are currently no genomic resources for the former, important group of amphibians. More widely applicable amphibian genomic data is urgently needed as more than two-thirds of known species are currently threatened or are undergoing population declines. We report a 5.8 Gbp (NG50 = 69 kbp) genome assembly of a representative North American bullfrog (Rana [Lithobates] catesbeiana ). The genome contains over 22, 000 predicted protein-coding genes and 6, 223 candidate long noncoding RNAs (lncRNAs). RNA-Seq experiments show thyroid hormone causes widespread transcriptional change among protein-coding and putative lncRNA genes. This initial bullfrog draft genome will serve as a key resource with broad utility including amphibian research, developmental biology, and environmental research. The globally-distributed Ranidae (true frogs) are the largest frog family. Here, Hammond et al. present a draft genome of the North American bullfrog, Rana (Lithobates )catesbeiana, as a foundation for future understanding of true frog genetics as amphibian species face difficult environmental challenges.